2019
DOI: 10.1007/s10815-019-01481-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centered elective egg freezing: a binational qualitative study of best practices for women’s quality of care

Abstract: Purpose How can elective egg freezing (EEF) be made patient centered? This study asked women to reflect on their experiences of EEF, which included their insights and recommendations on the optimal delivery of patient-centered care. Methods In this binational, qualitative study, 150 women (114 in the USA, 36 in Israel) who had completed at least one cycle of EEF were recruited from four American IVF clinics (two academic, two private) and three in Israel (one academic, two private) over a two-year period (June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 39 publications
(46 reference statements)
5
27
0
Order By: Relevance
“…In accordance with previous qualitative studies on SEF [20,38], we found that some participants felt discriminated against while reimbursement was not available. It is striking that some, being single, felt discriminated against based on their relationship status whereas Belgian compulsory health insurance covers single women in the same way as women in relationships if they undergo a full IVF procedure [39].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous qualitative studies on SEF [20,38], we found that some participants felt discriminated against while reimbursement was not available. It is striking that some, being single, felt discriminated against based on their relationship status whereas Belgian compulsory health insurance covers single women in the same way as women in relationships if they undergo a full IVF procedure [39].…”
Section: Discussionsupporting
confidence: 91%
“…However, research points out that women interested in elective egg freezing are often at the end of their reproductive life spans (late 30 s to early 40 s). These women want children, but have no partner with whom to build a family ( 57 ). Although the chances to have a child are rather low, the procedure is expensive (between 1500 €and 3000 €per cycle) and not affordable for everyone.…”
Section: Egg Preservationmentioning
confidence: 99%
“…This was associated with perceived lower adequacy of information and emotional support provided to the women, suggesting that better-quality information can help women in their deliberations about egg freezing and reduce the incidence of feelings of regret. Echoing this sentiment in the findings of their detailed qualitative interview study with 150 women who froze their eggs in the USA and Israel, Inhorn et al (2019) also highlighted the importance of making accurate and detailed information available. In fact, they identified the provision of clear and detailed information as a key component of their 11 specific dimensions constituting ‘best practice’ in ‘patient-centred elective egg freezing’.…”
Section: Discussionmentioning
confidence: 99%
“…She has argued for the importance of including as much accurate data as possible, as well as a discussion of remaining uncertainties as part of informed consent processes, writing, ‘Perhaps most important of all, potential egg freezers need to understand that even if eggs survive the thawing process, there are no guarantees that a future IVF cycle will be successful’. Currently, there is very little information about egg freezing on UK fertility clinic websites that would fulfil either the patient-centred criteria explained by Inhorn et al (2019) , or the legal and ethical requirements outlined by Jackson (2018) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation